Differences in Antegonial Index values in type II diabetes mellitus patients using panoramic radiography - Husnul Mariah; Norlaila Sarifah; Agung Satria Wardhana; Diana Wibowo; Irham Taufiqurrahman (Ikatan Radiologi Kedokteran Gigi Indonesia, 2023)
Objectives: This research is aimed to analyze the value of the antegonial index in patients with type II diabetes mellitus using panoramic radiography. Materials and Methods: This research is using stratified random sampling study with unpaired numerical comparative formula. The research sample was patients who were visiting and diagnosed with type II diabetes mellitus for ≤ 5 years and > 5 years by doctors at the Internal Diseases Polyclinic at Ulin General Hospital, Banjarmasin. Mandibular cortical thickness can be seen in the results of panoramic radiographs using radiomorphometric measurements with mandibular cortical index measurements, which is called as antegonial index. Antegonial index measurement as a screening tool can detect either the patient is positive or negative for having bone resoption. Results: The result showed average value of mandibular cortical thickness in patients with diabetes mellitus type II with a period of disease ≤ 5 years does not match the normal limit of > 3.2 mm, which is 2.57 ± 1.41 and the average value of mandibular cortical thickness in the group of patients with long period of disease > 5 years is 2.19 ± 0.76. Conclusion: Mandibular cortical thickness in patients with type II diabetes mellitus for ≤ 5 years and > 5 years is not within normal limits.